The Effects of a Single Electronic Music Improvisation Session on the Pain of Adults with Sickle Cell Disease: A Mixed Methods Pilot Study. (23rd May 2018) - Rodgers-Melnick, Samuel N; Matthie, Nadine; Jenerette, Coretta; Griest Pell, Tara J; Lane, Deforia; Fu, Pingfu; Margevicius, Seunghee; Little, Jane A
Abstract: Background: Adults with sickle cell disease (SCD) experience acute pain that is multidimensional. Despite recent improvements in treatment, pain management remains a significant challenge for these individuals. Music therapy interventions have the potential to address several dimensions of SCD pain, but they require systematic investigation. Objective: This study investigated feasibility and preliminary efficacy of a single-session electronic music improvisation with a music therapist to diminish pain intensity and improve pain relief and mood in adults with SCD. Methods: Using a three-group mixed methods intervention design, we randomized 60 adults with SCD to standard care plus one of three 20-minute study conditions: 1) electronic music improvisation with a music therapist (MT); 2) recorded music listening (ML); or 3) no intervention (control). Measures of pain intensity (VASPI), pain relief (VASPR), and mood (VASMOOD) were assessed before and after the study conditions, with a subset of MT and ML participants interviewed after measure completion. Results: Compared to control, MT produced significant improvements in VASPI (odds ratio (OR) = 5.12, P = 0.035) and VASMOOD (OR = 11.60, P = 0.005). ML produced significant improvements in VASMOOD compared to control (OR = 5.76, P = 0.040). Qualitatively, there were two prominent themes directly related to music: 1) ML and MT offered many positive and few negative effects; and 2) music therapists provided comfort beyond the music. Conclusions: Preliminary findings were promising and support the need for additional studies evaluating improvisational music therapy interventions for acute pain management in adults with SCD.